2020
DOI: 10.1111/os.12815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patellar Denervation on Anterior Knee Pain and Knee Function in Total Knee Arthroplasty without Patellar Resurfacing: A Meta‐Analysis of Randomized Controlled Trials

Abstract: The aim of the present study was to evaluate the effect of patellar denervation (PD) in preventing anterior knee pain (AKP) and improving knee function after total knee arthroplasty (TKA) without patellar resurfacing, and to help surgeons decide whether or not to use PD in TKA. Methods: The electronic databases of Pubmed, Embase, Cochrane, Web of Science, and Scopus were searched for all randomized controlled trials (RCT) comparing the outcomes of PD and no patellar denervation (NPD) in TKA without patellar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
(75 reference statements)
0
17
2
Order By: Relevance
“…Nevertheless, they have also reached mixed results, mainly due to the limited number of trials included and different methodologies. [12][13][14][15] The most recent meta-analysis published by Wang et al only included nine RCTs, and concluded that PD could reduce the prevalence of AKP as well as improve knee function in the early stage following TKR. 15 It is worth mentioning that several RCTs with high quality has been published recently, [16][17][18][19] and were not included and evaluated in previous meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they have also reached mixed results, mainly due to the limited number of trials included and different methodologies. [12][13][14][15] The most recent meta-analysis published by Wang et al only included nine RCTs, and concluded that PD could reduce the prevalence of AKP as well as improve knee function in the early stage following TKR. 15 It is worth mentioning that several RCTs with high quality has been published recently, [16][17][18][19] and were not included and evaluated in previous meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] The most recent meta-analysis published by Wang et al only included nine RCTs, and concluded that PD could reduce the prevalence of AKP as well as improve knee function in the early stage following TKR. 15 It is worth mentioning that several RCTs with high quality has been published recently, [16][17][18][19] and were not included and evaluated in previous meta-analyses. Therefore, we performed this systematic review and meta-analysis to re-evaluate the effects of PD on AKP and knee function after TKR.…”
Section: Introductionmentioning
confidence: 99%
“…TKA features osteotomy, soft tissue release, and deep surgical sites and can lead to exposure of the sensory nerve fibers located around the patella with insufficient protection of the soft tissues, forcing patients to endure severe postoperative pain [ 1 , 21 , 22 ]. The use of perioperative analgesia is of great significance for patients undergoing TKA to return to exercise and enhance recovery [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing literature, patellofemoral OA is the most common cause of anterior knee pain [ 40 ]. The WOMAC is an important tool for assessing anterior knee pain [ 41 , 42 ], which may explain why patellar osteophytes mediated the association between cartilage morphology and change in WOMAC pain. In the subgroup analysis stratified by vitamin D intervention or not, there were no significant associations between cartilage morphology and change in knee symptoms in the vitamin D group.…”
Section: Discussionmentioning
confidence: 99%